Microplastic stress in plants: effects on plant growth and their remediations - Jia, Li; Liu, Lining; Zhang, Yujing; Fu, Wenxuan; Liu, Xing; Wang, Qianqian; Tanveer, Mohsin; Huang, Liping (Frontiers in Plant Science, 2023)
Microplastic (MP) pollution is becoming a global problem due to the resilience, long-term persistence, and robustness of MPs in different ecosystems. In terrestrial ecosystems, plants are exposed to MP stress, thereby affecting overall plant growth and development. This review article has critically analyzed the effects of MP stress in plants. We found that MP stress-induced reduction in plant physical growth is accompanied by two complementary effects: (i) blockage of pores in seed coat or roots to alter water and nutrient uptake, and (ii) induction of drought due to increased soil cracking effects of MPs. Nonetheless, the reduction in physiological growth under MP stress is accompanied by four complementary effects: (i) excessive production of ROS, (ii) alteration in leaf and root ionome, (iii) impaired hormonal regulation, and (iv) decline in chlorophyll and photosynthesis. Considering that, we suggested that targeting the redox regulatory mechanisms could be beneficial in improving tolerance to MPs in plants; however, antioxidant activities are highly dependent on plant species, plant tissue, MP type, and MP dose. MP stress also indirectly reduces plant growth by altering soil productivity. However, MP-induced negative effects vary due to the presence of different surface functional groups and particle sizes. In the end, we suggested the utilization of agronomic approaches, including the application of growth regulators, biochar, and replacing plastic mulch with crop residues, crop diversification, and biological degradation, to ameliorate the effects of MP stress in plants. The efficiency of these methods is also MP-type-specific and dose-dependent.